Who is at risk of dissection or rupture in moderately dilated ascending aorta? - Oh, Pyung Chun; Kang, Woong Chol (Journal of Thoracic Disease, 2016)
Ascending aortic dissection is a catastrophic medical emergency. Increasing ascending aortic diameter is known to have a profound impact on rupture, dissection and death. Current practice guidelines recommend elective aortic surgery when the ascending aortic diameter reaches 5.5 cm to prevent the fatal complications (1-3). However, the observations from the International Registry of Acute Aortic Dissection (IRAD) have noted that 59% of type A dissection patients had ascending aortic diameter